2000
DOI: 10.4314/sajas.v30i3.3848
|View full text |Cite
|
Sign up to set email alerts
|

The effects of shade and shearing date on the production of Merino sheep in the Swartland region of South Africa

Abstract: A total of 497 Merino ewes were allocated to one of four experimental groups for the period 1996 to 1998. The treatments were designed to provide data on the effect of shade during an autumn lambing season and the effect of shearing prior to joining in September or prior to lambing in February. Dietary intake in shaded and control paddocks was similar, but animals in shaded paddocks consumed less water than those in control paddocks. Lambs born in shaded paddocks tended to be heavier at birth than those born i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Given that staple strength is known to be reduced by reproduction (Hinch et al, 1996;Cloete et al, 2000), this result was not entirely unexpected. The reason why it only involved 4-year old ewes is, however, not clear.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Given that staple strength is known to be reduced by reproduction (Hinch et al, 1996;Cloete et al, 2000), this result was not entirely unexpected. The reason why it only involved 4-year old ewes is, however, not clear.…”
Section: Discussionmentioning
confidence: 75%
“…demonstrated that wool of ewes subjected to pre-lamb shearing was more sound (P < 0.05) than that of ewes shorn before joining, with fewer mid-staple breaks (Cloete et al, 2000). The practice of pre-lamb shearing employed in the resource population used may thus well have contributed to the general soundness of the wool tested.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…According to previous research sheep with 1 inch fleece are more comfortable than sheep with less wool because wool fibres dissipate heat more rapidly. Sheep with long wool were reported to be less sensitive to solar heating than newly shorn animals (CLOETE et al, 2000;PICCIONE et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, present-day strains and types may differ in respect of basal nutrient requirements, making them more susceptible to heat stress (Cloete et al, 2000).…”
mentioning
confidence: 99%